Long-term effects of supportive therapy in periodontal patients treated with fibre retention osseous resective surgery. II: tooth extractions during active and supportive therapy - Gianfranco Carnevale (Blackwell Synergy, 2007)
Background: Long-term tooth retention is the main objective of periodontal treatment. The aim of this retrospective study was to describe the prevalence and reasons of tooth extraction during active periodontal therapy (APT) and supportive periodontal care (SPC) in periodontal patients. Material and Methods: Three hundred and four periodontal patients were examined. APT consisted of non-surgical periodontal treatment and fibre retention osseous resective surgery, where needed, to obtain no sites with PD43 mm. All patients participated in an SPC programme for 3–17 years (mean time 7.8 years). Results: At the initial examination, 45% of the patients had moderate periodontitis and 41% severe periodontitis. During APT, 576 teeth were extracted (7.5%). The main reason for tooth extraction during APT was the presence of advanced periodontal lesions (44%). The number of tooth extractions was higher in cases with severe periodontitis. Extracted teeth showed a mean bone loss of 76% of the total root length. During SPT, a total of 67 teeth were removed (0.9%) in a subgroup of 50 patients. The clinical problems were primarily related to the incidence of root fracture (48%) and secondarily to the progression of periodontal disease (30%). Conclusion: Prevalence of tooth extraction during APT is associated with the severity of periodontal disease. Tooth loss during supportive periodontal care may be negligible when a meticulous SPC programme is performed in patients where minimal probing depth is consequential to APT.